The sale and leaseback investments framework for Real Estate Investment Trusts (REITs) in Malaysia / Nur Lesya Firsya Johaimi Ling, Mohd Hasrol Haffiz Aliasak and Kartina Alauddin - Johaimi Ling, Nur Lesya Firsya; Aliasak, Mohd Hasrol Haffiz; Alauddin, Kartina (College of Built Environment, 2023)
Sale and leaseback investment has become one of the alternative ways for institutional investors such as Real Estate Investment Trusts (REITs) in purchasing existing properties with great value.